Nilai Dalam Mitos “Putri Duyung Di Telaga Lor” Desa Miru Lamongan - Jagad Nabilatul Sa’diyah; Resdianto Permata Raharjo (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
In oral literary stories this time we discuss the value of myths, basically myths or legends that live in society, sometimes they often happened in the past, but the proof is not concrete and may not really have happened but is just a fairy tale. The value contained in these myths is a form of treasure to enrich literary values that develop from generation to generation so that they can become stories for future children and grandchildren. The value contained in the story is how we must be able to apply the values of politeness norms in social life, because we live side by side with creatures other than us. In this research we used the approach used in oral literature research entitled social values in the Mermaid myth in Telaga Lor, namely using a descriptive qualitative oral literature approach. Primary data was taken by interviews. The sources interviewed were the community, village administrators or elders. Meanwhile, the literature study used was obtained from several internet sources. This technique uses document analysis, behavioral observation, and interviews. Ethnographers have a focus point in their research which includes intensive study of culture and language, a single field or domain, or a combination of historical methods, observation and interviews. Initially ethnography had its roots in the fields of anthropology and sociology. Yet practitioners today conduct ethnographic research in all forms.